Periostin expression and its supposed roles in benign and malignant thyroid nodules: an immunohistochemical study of 105 cases - Kimihide Kusafuka; Masaru Yamashita; Tomohiro Iwasaki; Chinatsu Tsuchiya; Aki Kubota; Kazuki Hirata; Akinori Murakami; Aya Muramatsu; Kazumori Arai; Makoto Suzuki (BMC, 2021)
Abstract Background Thyroid tumors are often difficult to histopathologically diagnose, particularly follicular adenoma (FA) and follicular carcinoma (FC). Papillary carcinoma (PAC) has several histological subtypes. Periostin (PON), which is a non-collagenous extracellular matrix molecule, has been implicated in tumor invasiveness. We herein aimed to elucidate the expression status and localization of PON in thyroid tumors. Method We collected 105 cases of thyroid nodules, which included cases of adenomatous goiter, FA, microcarcinoma (MIC), PAC, FC, poorly differentiated carcinoma (PDCa), and undifferentiated carcinoma (UCa), and immunohistochemically examined the PON expression patterns of these lesions. Results Stromal PON deposition was detected in PAC and MIC, particularly in the solid/sclerosing subtype, whereas FA and FC showed weak deposition on the fibrous capsule. However, the invasive and/or extracapsular regions of microinvasive FC showed quite strong PON expression. Except for it, we could not find any significant histopathological differences between FA and FC. There were no other significant histopathological differences between FA and FC. Although PDCa showed a similar PON expression pattern to PAC, UCa exhibited stromal PON deposition in its invasive portions and cytoplasmic expression in its carcinoma cells. Although there was only one case of UCa, it showed strong PON immunopositivity. PAC and MIC showed similar patterns of stromal PON deposition, particularly at the invasive front. Conclusions PON may play a role in the invasion of thyroid carcinomas, particularly PAC and UCa, whereas it may act as a barrier to the growth of tumor cells in FA and minimally invasive FC.